FUNK OSTENTAÇÃO AS A CULTURAL PEDAGOGY: MUSIC, CONSUMPTION AND THE PRODUCTION OF FEMALE SUBJECTIVITIES IN SCHOOL - Juliana Ribeiro de Vargas; Rodrigo Saballa de Carvalho (Editora da Universidade de Santa Cruz do Sul, 2016)
This article is the result of a research that, based on the Gender Studies and the contributions of Michel Foucault's studies, aims to analyze and discuss how discourses on gender, sexuality and consumption made visible by music of the genre known, in Brazil, as funk ostentação have operated in the constitution of subjectivities in a group of young female students of a public school system. The empirical material comes from participant observations, records in a field diary, analysis of music files stored on memory cards of mobile phones of the survey participants and conversation circles carried out with them. Analyses of the songs as well as of the conversation circles show that funk ostentação is an important cultural pedagogy that has been operating in the production of female subjectivities when it indicates a certain way of being a woman nowadays.